2022
DOI: 10.1016/j.taap.2021.115856
|View full text |Cite
|
Sign up to set email alerts
|

ZC3H4 promotes pulmonary fibrosis via an ER stress-related positive feedback loop

Abstract: BackgroundPulmonary brosis is the sequela of many pulmonary diseases, such as pneumoconiosis and idiopathic pulmonary brosis. The principal characteristics of pulmonary brosis comprise myo broblast proliferation, alveolar damage and deposition of extracellular matrix components, which causes abnormal lung structure remodeling and an irreversible decline in lung function; however, the detailed mechanisms remain unclear. The current study focused on the role of ZC3H4, a new member of the zinc nger protein family… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…C, control group; H, high-dose group; L, low-dose group; M, medium-dose group proliferation, 23 while ERS may block and inhibit the expression of ZC3H4 through miR-212. 13,24 Here, in mouse testes in vivo and in vitro, we found that circZc3h4-miR212 axis regulating Zc3h4 decreased gradually with growing PCM dose, resulting in reduced cell proliferation and heavier testicular damage.…”
Section: Discussionmentioning
confidence: 78%
“…C, control group; H, high-dose group; L, low-dose group; M, medium-dose group proliferation, 23 while ERS may block and inhibit the expression of ZC3H4 through miR-212. 13,24 Here, in mouse testes in vivo and in vitro, we found that circZc3h4-miR212 axis regulating Zc3h4 decreased gradually with growing PCM dose, resulting in reduced cell proliferation and heavier testicular damage.…”
Section: Discussionmentioning
confidence: 78%
“…5 C, D), which activates ERS. Based on the tunicamycin dose–response relationship experiment conducted by a previous research group [ 17 ], we set the concentration to 50 μM. Finally, when cells were pretreated with the ERS inhibitor salubrinal, the SiO 2 -CM-induced increases in ZC3H4 and NTRK2 levels were attenuated, suggesting that ERS participates in ZC3H4-mediated anoikis resistance in fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that ATF6 transcriptionally controls the expression of thioredoxin domain-containing protein 5 (TXNDC5), which promotes fibrosis by enhancing TGF-β signaling activity in kidney fibroblasts ( 89 ). ER stress can activate fibroblasts and promote pulmonary fibrosis through a positive feedback loop with ZC3H4, a recently discovered member of the CCCH-type zinc finger protein family ( 90 ). These data suggest that ER stress plays a crucial role in fibroblast activation and could be a potential target for regulating fibrosis in cGVHD ( Figure 1 ).…”
Section: The Contribution Of Upr In Gvhd Developmentmentioning
confidence: 99%